THE EFFECT OF NURSE PERCEPTION IN WORK INCENTIVE AND SATISFACTION SYSTEMS ON ORGANIZATIONAL CITIZENSHIP BEHAVIOR: A CASE STUDY AT GOVERNMENTAL HOSPITAL - Sinambela M.W.C.; Panjaitan N.K.; Dirdjosuparto S. (Russian Journal of Agricultural and Socio-Economic Sciences, 2019)
Hospital is a health service provider organization which always strives to provide satisfactory services so that customers continue to seek the Hospital's services to obtain the required health services. A hospital also demands loyalty from its employees. Therefore, behavior outside the job description (extra role) of the nurse is necessary in a hospital. One of the extra-role behaviors expected of the nurse by the hospital is organizational citizenship behavior (OCB). This study aims to analyze the influence of nurses' perceptions on incentive systems and job satisfaction on OCB. The number of respondents studied was 100 nurses in the inpatient care using a purposive sampling method. The method used in this study was structural equation model (SEM) with the partial least square (PLS) approach using SmartPLS 3.0 software. The results has shown that the perception of the nurses on the incentive system had an effect on the OCB through job satisfaction, so that a positive perception of the nurses on the incentive system would result in higher job satisfaction that would improve OCB.